Variation in wheat (Triticum aestivum) advance lines and released cultivars for traits associated with nitrogen use efficiency under N limiting environment - RANJAN, RUMESH; YADAV, RAJBIR; PANDEY, RENU; JAIN, NEELU; BAINSLA, NARESH KUMAR; GAIKWAD, KIRAN B; SINGH, ANJU M (The Indian Journal of Agricultural Sciences, 2019)
A subset of 19 genotypes was formulated on the basis of mean values for various traits related to nitrogen use efficiency from 175 genotypes comprising advance breeding lines and released Indian wheat (Triticum aestivum L.) cultivars observed under hydroponic condition. This subset was further evaluated in the pipe under nitrogen limiting environment for the various traits related to nitrogen use efficiency and other agronomic parameters. Variability study shows wide ranges of variation for the traits under studies. Nitrogen uptake efficiency (NUpE) shows more variation in comparisons to nitrogen utilization efficiency (NUtE) under N limiting condition. All of below ground and above ground traits except plant height shows positive correlation with nitrogen use efficiency (NUE). A positive correlation between shoot dry weight and root dry weight indicates no conflict for resource allocation and both can be simultaneously improved through selection in the breeding programme to improve NUE. Cluster analysis showed that cluster III found to be best performing for NUE trait and can be used in selection or to generate desirable genetic variability. In this study, the derivative of the cross HD 2967/DT 2761 show high root dry weight (RDW), shoot dry weight (SDW) and thus finally lead to high NUE under limiting N and can be used further in breeding programmes.